Association between Quality of Family Relationships and Social Anxiety (Investigating the Mediating Role of Family Cohesion) - Hossein Keshavarz Afshar; Razieh Safarifard; Mehrsa Hosseini; Zahra Hodhodi (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Family relationships have a major role on the behavior of children, so, this study aimed at investigating the association between quality of family relationships (parental conflict, sister brotherhood relationships, and parenting styles) and social anxiety while considering the mediating role of family cohesion. Materials and methods: The research population included all high school girls in Karaj, Iran among whom 250 were selected using multi-stage cluster sampling. The participants completed Social Anxiety Scale for Adolescents (SASA), Family Confidence Questionnaire (FCS), Conflict Tactics Scale (CTS), Index Brother or Sister Relationship (IBR or ISR), and Baumrind Parenting Style Index (BPSI). The path analysis was conducted to investigate the mediating role of family. Results: The findings showed a significant positive correlation between social anxiety and parental conflicts and authoritative parenting style (p<0.05). But, there was a significant negative correlation between social anxiety and the quality of sibling relationships (p<0.05). The mediating role of family cohesion was confirmed only between the quality of sibling relationships and social anxiety. In this research, 60% of social anxiety variance was explained through the variables in the model proposed. Conclusion: It is believed that the quality of family relationships (parental conflicts, the quality of sibling relationships, and the authoritative parenting style) and family cohesion could be used for theoretical explanations and psychological treatments in people with social anxiety.